Pembuatan Website pada Perusahaan "Sky High Tour & Travel Agency" - Machael Cahyadi; Agustinus Noertjahyana; Silvia Rostianingsih (Jurnal Infra, 2016)
Sky High Tour & Travel Agency is a tour company and travel agency in the area of South Surabaya, which offers services in the field of Tourism. Sky High Tour & Travel Agency is planning to have a website that can be used as a user friendly, offers package tours & travel, leaving a message / note, and login to the customer so that it can make a reservation (reservation).This website is created by using the programming language PHP and MySQL as data storage / database. Website created based on company needs a way to find information and data through consultation / interview so that it can determine the scope of the company. The scope of the following: the reservation process, sales, login to the customer who registers as a member, leave a note / FAQ that has been provided and a website that is user friendly for customers.The test results of the application shows that these websites can automatically process administrative data directly related to the reservation and sales process. Reports generated applications reached 75% of respondents in accordance with company requirements. The level of accuracy of the information and data reached 100% of respondents. While the benefits of an application to get the 100% of respondents.